Development of an electric cum solar oven and study of its performance - GEORGE, K. O; Mohammed Raphy; Padmakumar, V. T; Raj Mohan, C. K (Tavanur Kelappaji College of Agricultural Engineering and Technology, 1991)
project report
project report
Keywords: project report